Pilocarpine induces an increase in the anterior chamber angular width in eyes with narrow angles. Issue 5 (1st May 1999) - Kobayashi, Hiroshi; Kobayashi, Kaori; Kiryu, Junichii; Kondo, Takehisa
Abstract : AIM: To determine the mechanical effects of pilocarpine on the trabecular-iris angle opening in eyes with narrow angles, compared with its effects on healthy control subjects with wide angles. METHODS: A narrow angle was defined as 25° or less of trabecular-iris angle on ultrasound biomicroscopic examination. The change in anterior chamber depth (ACD), trabecular-iris angle (TIA), angle opening distance (AOD, distance between trabecular meshwork and iris) measured at 250 μm and 500 μm from the scleral spur (AOD250 and AOD500), and iris thickness was determined in 30 eyes of 30 patients (13 men and 17 women, between 63 and 82 years (mean 70.4 years)) with narrow angles and in 30 sex and age matched control subjects with wide angles before and 1 hour after the instillation of 2% pilocarpine hydrochloride by ultrasound biomicroscopy. RESULTS: In all eyes with narrow angles, pilocarpine increased the TIA, AOD250, and AOD500; these changes increased significantly and linearly as the corresponding pretreatment values decreased ( r = 0.807, p = 0.0001; r = 0.787, p = 0.0001; r = 0.852, p = 0.0001). Of 30 eyes with wide angles, 23 eyes whose ACD was 2670 μm and more showed a decrease in the TIA, AOD250, and AOD500; the changes in TIA, AOD250, and AOD500 also significantly correlated with the corresponding pretreatment values ( r = 0.913, p = 0.0001; r = 0.882, p = 0.0001; r = 0.895, p = 0.0001). Pilocarpine induced a smaller decrease in ACD in eyes with narrow angles than in those with wide angles (p = 0.0001). There was a linear correlation between the increase in ACD change and the decrease in pretreatment ACD in eyes with narrow angles and those with wide angles ( r = 0.781, p = 0.0003; r = 0.798, p = 0.0001). CONCLUSIONS: The finding that pilocarpine increases angular width in patients with narrow angles indicates that this agent is useful for treating patients with narrow angles and angle closure glaucoma. The prediction of the pilocarpine induced change in the angle may assist ophthalmologists in treating such patients.